Impact of oxygen concentration changes on ANGPTL8 expression of human pulmonary artery endothelial cells - ZHANG Zongli, LI Tao, MA Jingwen, ZHANG Jiaxin, LI Xingchao, XI Shibing (Jichu yixue yu linchuang)
Objective To explore the impact of change in oxygen concentration on the expression of angiopoietin-like protein 8 (ANGPTL8) by endothelial cells (HPAECs) of human pulmonary artery, and the role and mechanism of ANGPTL8 in pulmonary hypertension (PH). Methods HPAECs were treated under hypoxic and hyperoxic conditions, and the expression level of ANGPTL8 was detected using Western blot and PCR. The changes in endothelial-mesenchymal transition (EndMT) and ERK signaling pathway activity were analyzed. Simultaneously, newborn rats were exposed to hyperoxia to develop a bronchopulmonary dysplasia (BPD) model. The expression of ANGPTL8 protein and changes in the ERK signaling pathway in lung tissue were observed. Results Under hypoxic condition, the protein expression of ANGPTL8 in HPAECs was significantly increased accompanied by inhibition of the ERK signaling pathway. ANGPTL8 promoted the EndMT process induced by hypoxia(P＜0.05) and silencing the expression of ANGPTL8 resulted in a partial reversal of EndMT. The protein expression of ANGPTL8 was decreased in hyperoxia-exposed HPAECs and rat lung tissues accompanied by the activation of the ERK signaling pathway(P＜0.05). Conclusions ANGPTL8 is highly sensitive to the change of oxygen concentration in HPAECs and closely correlated to its expression level and to the activity of ERK signaling pathway. This result suggests that ANGPTL8 may have potential regulatory effects on the development of PH.